Kronika działalności TMMB 2010/2011 (Kronika Bydgoska, 2010)
The chronicie is a comprehensive register of all the most important initiatives and enterprises of the Friends of Bydgoszcz Association from the middle of 2010 to almost the end of 2011. Particularly detailed are educational trips under the banner “Bydgoszcz behind closed doors”, efforts aimed at establishment of the Bydgoszcz Metropolis, celebrations of the 180th anniversary of the association’s existence, and its abundant publishing activity.